Case report: Immunoadsorption therapy for anti-caspr1 antibody-associated nodopathy - Liu, Lili; Chen, Juanjuan; Zhang, Yue; Wu, Jun; Hu, Jun; Lin, Zhijian (Frontiers in Immunology, 2022)
Several autoantibodies against proteins located at nodes of Ranvier have been identified in patients with chronic inflammatory demyelinating polyneuropathy (CIDP) in the last few years (1). These autoantibodies include anti-neurofascin, anti-contactin1 (CNTN1), and anti-contactin-associated protein 1 (Caspr1) antibodies.Nodo-paranodopathies are a recently classified group of diseases with autoantibodies against node of Ranvier proteins. In our case report, we describe a patient with anti-Caspr1 antibody-associated nodopathy who achieved a good response to immunoadsorption therapy.This case expands our understanding of anti-Caspr1 antibody-associated nodopathies and provides evidence for IA therapy in these diseases.